ANALISIS PENGARUH PEMASARAN 4A TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ERIGO DI SHOPEE - Carolus Dimas Wijanarko (Jurnal Administrasi Bisnis, 2024)
Erigo is a popular local clothing brand in Indonesia. Erigo carries the concept of traveling with the theme of street style. Erigo's achievements are Top Local Brand & Top Fashion Brand from the Shopee Super Awards from September 2020 to December 2020, a MURI record for selling the most shirts online within one hour and participating in New York Fashion Week 2022. From a buyer's point of view, Erigo often skips things such as products that are not suitable for use, damaged, and exchanged, thus making consumers dissatisfied. The purpose of this study was to analyze the 4A marketing (acceptability, affordability, accessibility, and awareness) of the purchasing decisions of Erigo consumers at Shopee. Marketing 4A is a tool that helps marketers to align marketers’actions with the four important values that customers are looking for. This research method is descriptive research with a quantitative approach. Respondents totaled 100 people with the criteria of having bought Erigo products through the Shopee e-commerce platform. The results of the f-test indicate that the independent variable has a simultaneous effect on the dependent variable. The results of the t-test show that acceptability and accessibility do not have a significant effect and affordability